ANALISIS PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAN ARSITEKTUR KANTOR PERWAKILAN BANK INDONESIA PROVINSI PAPUA BARAT MENGGUNAKAN METODE TIME STUDY: ANALYSIS OF LABOR PRODUCTIVITY IN ARCHITECTURAL WORK AT THE OFFICE OF THE BANK OF INDONESIA REPRESENTATIVE IN WEST PAPUA PROVINCE USING THE TIME STUDY METHOD - Defanty Kusgita Rachmantary; Mayang Kinanti Puteri; Puspita Utari (Universitas Papua, 2025)
Labor productivity determines the success of the construction project schedule; however, in some projects, the actual productivity in the field differs from the SNI. This research analyzes labor productivity in wall architecture work in the Bank Indonesia West Papua Office Development project, compared to the 2016 and 2022 SNI AHSP. The purpose is to analyze worker productivity, its influencing factors, and compare field productivity with SNI 2016 and 2022 using the time study method, which is a standard measurement of time based on basic time observations to calculate productivity. As a result, the productivity of masonry was 98.64 m²/OH, wall plastering 58.18 m²/OH, and wall acian 42.51 m²/OH. Field productivity is higher than the 2016 SNI by 2.32 times (masonry), 3.12 times (plastering), and 2.93 times (acian), respectively. Factors affecting productivity include weather, material conditions, number of workers, work location, and labor experience.